Pengaruh Kualitas Pelayanan Dan Kelengkapan Sarana Prasarana Terhadap Kepuasan Pasien Penyintas Covid-19 (Studi Pada Safe House Kepanjen) - Filla Luih Candrani; Pardiman Pardiman; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of Service Quality, and Completeness of Infrastructure on Patient Satisfaction of Covid-19 Survivors at Kepanjen Safe House. The sampling technique used was random sampling to obtain a sample of 64 respondents. Methods of data collection using a questionnaire. The data analysis technique used in this research is multiple linear regression. The results showed that partially the quality of service had no effect on patient satisfaction, but for infrastructure it had an effect on patient satisfaction. If simultaneously the quality of service and infrastructure have a significant effect on patient satisfaction. Keywords: Service Quality, Infrastructure, Patient Satisfaction.